Praktek Perkawinan Muhallil di Padarincang Serang Provinsi Banten Indonesia - Ahmad Sanusi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This paper to analyse about muhallil marriage, which is carried out as a requirement to be allowed remarry between ex-husband and ex-wife, that has been talaq bain ( divorced three times) in Padarincang District, Serang Regency, Banten Province. This juridical empirical research uses qualitative. Data collection techniques using observation, interviews and documentation studies. The analysis technique uses an interactive model. The results show that the practice of muhallil marriage in Padarincang District was different from the existing provisions, because the ex-husband had to find the penyelang to ex-wife, then agreed by paying the penyelang and limiting the time of marriage. The ex- husband also forced the penyelang to divorce his wife, so that he could immediately remarry his ex-wife without waiting for the iddah period to end. According to Islamic law, marriage is haram and illegitimate, except it is carried out in earnest by Islamic law. Based on these facts, socialization and awareness should be carried out in the community about muhallil marriage, so that there is no violation of Islamic law and positive law.